KAJIAN NAUNGAN, TARAF PUPUK UREA DAN VARIETAS KEDELAI (Glycine max L.) TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KEDELAI SEBAGAI TANAMAN SELA DI AREAL PERTANAMAN KELAPA SAWIT MENGHASILKAN - Napitupulu Asima (Jurnal Pertanian Tropik, 2017)
The aims of this research were to analyze morpo_physiology changing of soybean underthe oil palm area; determine the effect of shading and N fertilizer dosage on the growth and yieldof soybean under the oil palm area, and determine suitable soybean varieties that enablegrow and produce under oil palm. The experiment located in Ujung Labuan Village, DeliSerdang District. The experiment was arranged in Split-split Plot Design 3 x 4 x 3 with3 replication, with three factors observed: 1) shade level, consist of: under 4 years oldoil palm, under 6 years old oil palm, open area, 2) N dosage: 200 kg urea/ha, 150 kg/ha,100 kg urea/ha, 0 kg urea/ha, 3) soybean variety: Anjasmoro, Burangrang, andGrobogan. Plant height, leaf area, plant dry weight, and soybean production weredetermined. The result showed there were some significant effects of interaction factorsbetween oil-palm canopy shading, N dosage and soybean variety on growth and yield ofsoybean. The highest growth and production of soybean found in open areas. Between 4years old oil palm and 6-7 years old oil palm, soybean growth, and production areinsignificant different and lower than those on the opening area. N dosage makes somesignificant effects on growth and yield of soybean, which is usually nonsignificantbetween 150 kg Urea/ha or 200 kg Urea/ha. Meanwhile, soybean variety makes somesignificant effects. At the open area, burangrang make the highest growth and production byapplication of 200 kg urea/ha, but under oil palm, the highest production found atBurangrang under 4 years old oil palm and application of 200 kg urea/ha, followed byseveral treatments that are insignificantly different.